HMGB1 Aggravates Pressure Overload-Induced Left Ventricular Dysfunction by Promoting Myocardial Fibrosis. (17th June 2020) - Zhang, Lei; Yu, Ying; Yu, Peng; Wu, Jian; Sun, Aijun; Zou, Yunzeng; Su, Yangang; Jiang, Hong; Ge, Junbo
Abstract : Aim . Fibrosis had important effects on pressure overload-induced left ventricular (LV) dysfunction. High-mobility group box 1 (HMGB1), which was closely associated with fibrosis, was involved in the pressure overload-induced cardiac injury. This study determines the role of HMGB1 in LV dysfunction under pressure overload. Methods . Transverse aortic constriction (TAC) operation was performed on male C57BL/6J mice to build the model of pressure overload, while HMGB1 or PBS was injected into the LV wall. Cardiac function, collagen volume, and relevant genes were detected. Results . Echocardiography demonstrated that the levels of LV ejection fraction (LVEF) were markedly decreased on day 28 after TAC, which was consistent with raised collagen in the myocardium. Moreover, we found that the exposure of mice to TAC + HMGB1 is associated with higher mortality, BNP, and collagen volume in the myocardium and lower LVEF. In addition, real-time PCR showed that the expression of collagen type I, TGF- β, and MMP2 markedly increased in the myocardium after TAC, while HMGB1 overexpression further raised the TGF- β expression but not collagen type I and MMP2 expressions. Conclusion . This study indicated that exogenous HMGB1 overexpression in the myocardium aggravated the pressure overload-induced LV dysfunction by promoting cardiac fibrosis, which may be mediated by increasing the TGF- β expression.